Book review. Shaked N (2022) Museums and Wealth: The Politics of Contemporary Art Collections - Amanda Tobin Ripley (The February Journal, 2025)
This review focuses on Nizan Shaked’s Museums and Wealth: The Politics of Contemporary Art Collections (2022) and its dissection of the system of philanthrocapitalism in the financing of museum operations. The review asserts the importance of engaging with Shaked’s analysis as a means of recognizing the complicity of museum workers with these systems of wealth accumulation. Shaked demonstrates how existing systems of philanthropic giving uphold white supremacy and imperial hegemony by concentrating wealth and decision-making power in the hands of boards of trustees. To enact liberatory museum practices and ethics, therefore, museum workers and activists must also transform funding and governance.